Karakteristik Pasien Pasca-Apendektomi di Rumah Sakit Umum Daerah Tabanan - I Komang Ardhika Gunawan; Ni Putu Diah Witari; Ni Wayan Rusni; Ni Wayan Armerinayanti; Gde Candra Yogiswara; Ade Dwi Mahendra; I Gusti Ngurah Fajar Viwakananda; Made Bramastya Nugraha Teja Kusuma Mulyawan (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Acute appendicitis is one of the most common abdominal surgical emergencies, primarily managed through appendectomy. Post-appendectomy patients require further hospitalization, where indicators such as length of stay, leukocyte levels, and pain intensity are essential to evaluate clinical outcomes. This study aims to describe the characteristics of post-appendectomy patients at Tabanan General Hospital (BRSU Tabanan) in 2023–2024. This research used a descriptive observational design with a cross-sectional approach, and data were collected retrospectively from medical records. Samples were selected using consecutive sampling, with a total of 120 patients who met the inclusion and exclusion criteria. Data were analyzed univariately and presented in frequency distributions and mean values.The results showed that the mean age of patients was 34.73 ± 13.62 years, with a higher proportion of females (56.7%) compared to males (43.3%). The mean leukocyte count was 12.65 ± 4.22 ×10³/µL, with most patients (56.7%) categorized as mild leukocytosis. The mean length of stay was 2.83 ± 1.54 days, with 93.3% of patients classified as having a short hospitalization period (≤5 days). Most patients had no comorbidities (85%), while hypertension was the most common comorbid disease (61.1%). The mean Visual Analog Scale (VAS) score before appendectomy was 5.34 ± 0.96 (moderate pain), which decreased to 2.42 ± 0.63 (mild pain) after surgery.